Efektivitas Modul Komunikasi Interprofesional Pada Mahasiswa Fakultas Kedokteran dan Keperawatan - Rensa Rensa; Kristina Lisum; Jesika Pasaribu; Sri Indiyah (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Interprofessional education (IPE) is one of medical professionals’ need to manage the patients’ problem efficiently and comprehensively.Method: This is a cohort prospective study that implemented mixed methods approach that consists of quantitative and qualitative methods. Quantitative data is collected through the Interprofessional Collaborative Competencies Attainment Survey (ICCAS) on pilot study, while qualitative data is collected through the open-ended questions on Focus Group Discussion (FGD). This study involves students from Medical School, Atma Jaya Catholic University and Sint Carolus Nursing School, all of them were at their fourth-year college.Results: Pilot study obtains quantitave data from the ICCAS questionnaire, before and after Interprofessional Learning (IPL) intervention. There are mean differences on domain collaboration before and after IPL intervention using interprofessional communication module (mean difference 6 [95%CI 2 to 10], P 0,007).Conclusion: There are significant differences in collaboration skills between FKUAJ and STIK’s college students after IPL.